LEARNING QUALITY MANAGEMENT AT SMP DARUL ARQAM GOMBARA MAKASSAR - Martini, Martini; Mus, Abdul Rahman; Hakim, Ahmad; Syahid, Akhmad (Program Pascasarjana, UIN Alauddin Makassar, 2021)
This study examined in depth the management of learning quality by looking at the four management components, namely Planning, Organizing, Actuating, and Controlling (POAC) at SMP Darul Arqam Gombara Makassar. The research uses a qualitative phenomenological approach, with the type of research being a multi-site study. Data collection techniques through questionnaires, interviews, observation and documentation. The data were analyzed using an interactive analysis model consisting of data collection, data reduction, data presentation, verification, and conclusions. This study indicates that learning quality management at SMP Darul Arqam Makassar is implemented through four steps. First, learning planning according to Process Standards with innovative and accelerated curriculum content with the demands of the current education